Sharp and Tunable Crystal/Fano‐Type Resonances Enabled by Out‐of‐Plane Dipolar Coupling in Plasmonic Nanopatch Arrays. Issue 10 (28th August 2018) - Taghinejad, Mohammad; Taghinejad, Hossein; Malak, Sidney T.; Moradinejad, Hesam; Woods, Eric V.; Xu, Zihao; Liu, Yawei; Eftekhar, Ali A.; Lian, Tianquan; Tsukruk, Vladimir V.; Adibi, Ali
Abstract: Tuning resonance lineshapes of plasmonic structures is essential to create customized media with compelling optical properties for optimized light–matter interactions. The diversity of available metals and the variety of design architectures provide a rich portfolio for statically controlling the resonance lineshape. However, dynamic tuning of resonance attributes (e.g., the resonance wavelength and linewidth) are yet to be more expanded, especially when a narrow resonance linewidth is on demand. Here, using a plasmonic nanopatch array, sharp plasmonic crystal (PC) resonances are demonstrated across a wide spectral range of 230 nm, with full‐width at half‐maximum of only ≈6 nm. The combination of angle‐resolved ellipsometry and full‐wave simulations shows that diffractive coupling of out‐of‐plane electric dipoles is the principal contributor in the formation of such sharp PC resonances. In addition, the designed nanopatch PC supports a plasmonic Fabry–Pérot‐like resonance that can be interfered with the PC resonance to generate complex Fano‐type lineshapes. The coexistence of tunable resonance features renders the designed structures as a rich platform for applications seeking enhanced light–matter interactions and optical signal processing. Abstract : Diffractive coupling of out‐of‐plane electric dipoles in plasmonic nanopatch arrays is employed to demonstrate exceptionally narrow plasmonic crystal resonances (full‐width at half‐maximum ≈ 6 nm). The combination of spectroscopic ellipsometry and full‐wave simulations shows accurate control over the resonance wavelength of the plasmonic crystal modes by controlling the in‐plane momentum of the excitation light via the angle of incidence.